Checkpoint blockade in cancer immunotherapy - Allison, James (Henry Stewart Talks, 2007)
Activation of naive T-cells, CD28 and CTLA-4, Differential regulation of T-cell responses, Responding repertoire, Biological role of CTLA-4, Tumor-specific immune responses, Treg activity, CTLA-4/GVax, Immunotherapies, Conventional therapies, Ipilumumab, Clinical studies: melanoma, Reversible immune mediated toxicity